Short communication. Employment of molecular markers to develop tetraploid “supermale” asparagus from andromonoecious plants of the landrace ‘Morado de Huétor’ - Regalado, Jose J.; Gil, Juan; Castro, Patricia; Moreno, Roberto; Lopez-Encina, Carlos (Spanish Journal of Agricultural Research, 2014)
The aim of this work was the development of new “supermale” genotypes retaining the highest genetic diversity possible of the tetraploid asparagus landrace ‘Morado de Huétor’. The elite andromonoecious male HT664 of the ‘Morado de Huétor’ asparagus landrace and the andromonoecious hybrid male HC027, obtained by crossing between this landrace and a commercial cultivar of Asparagus officinalis, were selected for self-pollination to produce possible “supermales” with genes of ‘Morado de Huétor’ (SMHT). To confirm the hybrid nature of HC027, we characterized this genotype with EST-SSR (Expressed Sequence Tag-derived Simple Sequence Repeats) markers. We also adopted the sex-linked marker Asp1-T7 for sex determination in ‘Morado de Huétor’ and the resulting hybrids between this landrace and other commercial cultivars. Asp1-T7 marker was used for the selection and genotyping of SMHT. “All-male” cultivars with a different genetic background can be generated by crossing females with these new “supermale” genotypes, and the agronomical traits of these new cultivars would be very different from the “all-male” cultivars currently available in the market, making them extremely interesting for asparagus breeding programs.